When Ukrainian migrant meets a Polish official: Implementing migration policy in the opinions of temporary economic migrants from Ukraine in Poland in a neo-institutional perspective - Szaban, Dorota; Michalak, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Migration processes affect the functioning mechanisms of many institutions and public spheres, on which the state create particular public policies. Migration policy is one of them. The success of its implementation depends on many factors, but institutional actors (officials) play a crucial role in this process.
Keywords: neo-institutionalism; migration policy; migration from Ukraine; determinants of migration decisions; the role of an official in the adaptation process of migrants